Complexity Matters: On Gender Agreement in Heritage Scandinavian - Johannessen, Janne Bondi; Larsson, Ida (Frontiers in Psychology, 2015)
This paper investigates aspects of the noun phrase from a heritage language perspective, with an emphasis on noun phrase-internal gender agreement and noun declension. Our results are somewhat surprising compared with earlier research: We find that noun phrase-internal agreement for the most part is rather stable. To the extent that we find attrition, it affects agreement in the noun phrase, but not the declension of the noun. We discuss whether this means that gender is lost and has been reduced to a pure declension class, or whether gender is retained. We argue that gender is actually retained in these heritage speakers. One argument for this is that the speakers who lack agreement in complex noun phrases, have agreement intact in simpler phrases. We have thus found that the complexity of the noun phrase is crucial for some speakers. However, among the heritage speakers we also find considerable inter-individual variation, and different speakers can have partly different systems.